2022
DOI: 10.26434/chemrxiv-2022-6qpb8-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solvated Electrons! The Missing Link in Highly Reducing Photocatalysis

Abstract: In recent years, in-situ generated organic radicals have been used as highly potent photoinduced electron transfer (PET) agents resulting in catalytic systems as reducing as alkaline metals that can activate remarkably stable bonds. However, the transient nature of these doublet state open-shell species has led to debatable mechanistic studies, hindering adoption and development. Herein, we document the use of an isolated and stable neutral organic radical as a highly photoreducing species with a reduction pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The Gianetti group reported such a reaction by employing n Pr-DMQA + − BF 4 as a conPET catalyst (Scheme 69). 186 Under blue light irradiation, n Pr-DMQA + − BF 4 was able to activate chloroarenes 64 with pyrrolidine as the sacrificial reductant. Both aryl chlorides bearing electron-withdrawing (CN, CF 3 ) and -donating (OMe, Me) groups can be reduced to the corresponding aryl radicals.…”
Section: Photoredox Catalysismentioning
confidence: 99%
“…The Gianetti group reported such a reaction by employing n Pr-DMQA + − BF 4 as a conPET catalyst (Scheme 69). 186 Under blue light irradiation, n Pr-DMQA + − BF 4 was able to activate chloroarenes 64 with pyrrolidine as the sacrificial reductant. Both aryl chlorides bearing electron-withdrawing (CN, CF 3 ) and -donating (OMe, Me) groups can be reduced to the corresponding aryl radicals.…”
Section: Photoredox Catalysismentioning
confidence: 99%
“…[11b] Miyake and co-workers demonstrated an excellent arene reduction protocol enabled by a tailored organic photoredox catalyst which operated through two consecutive photoinduced single electron transfers. [11c] Key to the success of these methods is the harvesting of the energy of two photons, optionally in combination with a sacrificial reductant, to create highly reducing conditions (reductive potential of catalytic system low to À 3.5 V vs. SCE [12] ). [13] Despite the notable reaction efficiency, the highly reducing conditions still resulted in chemoselectivity issues.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, even though DMF and DMSO dissolve the Gd(OTf) 3 salt very well, the reaction is completed suppressed (entries 8-9), presumably due to competing coordination of the solvents over the substrate 1 a. Other hydrogen atom donor reagents such as silane, stannane, thiophenol, HCO 2 Na, triphenylmethane, 9H-fluorene and 9,10-dihydroanthracene didn't produce the desired product (entries[10][11][12][13][14][15][16]. Control experiments revealed that both visible light and an inert atmosphere were essential to the reaction (entry 17).…”
mentioning
confidence: 99%
“…However, as the energy is reduced in the process of generation of a reactive photocatalyst, [5] the photocatalytic systems with single photon‐absorbing process always show limited power for reduction (generally > −2.2 V vs SCE) and thus are difficult to realize challenging carboxylation of reluctant substrates with low reduction potentials. In contrast, consecutive photo‐induced electron transfer (ConPET), which involves absorption of two photons within a single catalyst turnover and thus can achieve low reduction potentials (low to around −3.4 V vs SCE), [6l] has been proved to be a powerful strategy in organic synthesis [6, 7] . Although ConPET might be able to address such challenges (Scheme 1B), it has rarely been investigated in carboxylation with CO 2 [7]…”
Section: Introductionmentioning
confidence: 99%